Total cost of care of hematologic malignancy episodes versus target price under the Oncology Care Model. Issue 28 (1st October 2022) - Nguyen, Jennifer; Walsh, Karen; Maio, Vittorio; Park, Seojin; Patel, Shivangi; Keith, Scott W.; Handley, Nathan; Csik, Valerie Pracilio
Abstract : 67 Background: In 2016 the Center for Medicare & Medicaid Innovation developed the Oncology Care Model (OCM) in response to increasing cancer-attributable cost for medical services and prescription drugs. Under the OCM, practices are incentivized to provide higher quality and coordinated care through a dual payment model including a Monthly Enhanced Oncology Services (MEOS) payment and potential for performance-based payment (PBP), where PBPs are based on a practice's total cost of care (TCOC) savings amount relative to a risk-adjusted target amount. On average, hematologic malignancies are burdened with higher costs than other cancer types. The objective of this study was to evaluate whether TCOC and target price were aligned in OCM hematologic malignancy episodes. Methods: This was a retrospective cross-sectional study using OCM claims data from an urban, academic, National Cancer Institute-designated cancer center. The analysis was conducted at the episode level from performance period 1 to 4 (time period: 7/1/2016 to 7/1/2018). A logistic regression with a generalized estimating equation (GEE) was used to assess the likelihood of episode characteristics and TCOC to exceed the target price. A linear regression with a GEE was used to evaluate the mean difference between TCOC and target price episodes. Results: Of the 516 episodes of hematologic malignancies included in the analysis, 55.2% were male and 26.9% were 70-74 years old. 283 episodes (54.8%) exceeded target price. Several parameters were found statistically significantly associated with the likelihood of exceeding and not exceeding target price (Table). Largest positive mean difference from target price was in episodes with Medicare Part D drug use (24, 344) and largest negative difference in radiation use (-33, 758). Conclusions: We found a substantial misalignment between TCOC and target price for hematologic malignancy episodes, with a majority of episodes exceeding target price. This study adds to the existing evidence on the lack of adequate adjustment to the OCM target price. As the OCM concludes, our findings identify areas of opportunity for consideration in future payment models, such as re-evaluating the target price methodology, inclusion of drug costs and adequate adjustment for select parameters (history of chemotherapy, novel therapy, and Part B and D expenditures).GEE likelihood of exceeding target price. Parameter Odds Ratio (95% CI) Medicare Part B Drug (yes v. no) 1.94 (1.03-3.63) Medicare Part D Drug (yes v. no) 7.26 (3.99-13.18) Full Dual Status Enrollment (yes v. no) 0.35 (0.13-0.93) Home Health Agency (yes v. no) 2.55 (1.41, 4.61) > 730 Days from Last Chemotherapy (> 730 v. 0-61 days) 2.38 (1.35-4.20) Novel Therapy (yes v. no) 1.72 (1.01-2.94) HCC Flags (reference = 0 Flags) 2 3 4-5 6+ 0.34 (0.17-0.67) 0.40 (0.19-0.85) 0.26 (0.13-0.51) 0.18 (0.08-0.42) Radiation (yes v. no) 0.30 (0.11-0.81)